Writing on the Gospel of Mark - Telford, W.R. (Guides to Advanced Biblical Research, 2009)
This thorough manual for advanced students and their supervisors, and anyone researching or writing on the Gospel of Mark, is the opening volume in an important new series of Guides to Advanced Biblical Research. Together with an essay on the current state of research and a discussion of the future of Markan study, it provides a chrestomathy of samples of Markan research together with a review of recent dissertations and a full, annotated bibliography.